Integrating ESG in Shariah stock screening: viability and impacts - Adam Sa'ad, Auwal; Hasan, Aznan; Mohd Saufi, Sofiah; Misman, Siti Nursyawani; Ahmad Azhari, Farhana Anis; Munira, Abu Bakar (Routledge, 2025)
Shariah-compliant equity investors rely on a Shariah screening process to verify the compliance status of a specific stock with Shariah principles. Nonetheless, due to the lack of explicit focus on sustainability in the current Shariah stock screening process, the environment, social, and governance (ESG) motivated investors may be drawn to the traditional sustainability arena instead of the Shariah arena which can further result in slower investment rate in Shariah-compliant funds. Consequently, ESG-driven investors require an ESG screening to assess a company’s involvement in ethical initiatives before considering an investment. However, as a Muslim both are equally important as the principles of ESG and Shariah screening converge and uphold comparable values of responsibility, accountability, and stewardship, with the aim of safeguarding and benefiting the environment and humanity as a whole. This conceptual chapter that mainly focused on secondary data proposes integrating the ESG framework into Shariah stock screening as a means to enhance compassion towards the environment and humanity, aligning with the broader objectives of Maqasid Shariah. By considering the aspects of faith, self, intellect, posterity, and wealth, implementing ESG in the Shariah stock screening framework can help protect and preserve the necessities emphasised by Maqasid Shariah. This demonstrates that incorporating both screening components will not only enhance Islam but also improve performance as well. This chapter reviews the previous literature on Shariah screening methodology, ESG screening elements, and the performance of some institutions that integrate ESG screening with Shariah screening. The study recommends further research on the implementation of ESG in the Shariah stock screening framework to integrate Maqasid Shariah in every aspect of life.